Theory building in educational research - Kettley, Nigel C. (Continuum International Pub. Group, 2010)
This volume provides comprehensive guidance on the subjects of concept generation and theory building in educational research. By deploying the conceptual, methodological and theoretical principles of the Cambridge School of Sociology, that underpin a range of contemporary empirical research, the author shows how theory building, and theory, in contemporary educational research is in a state of crisis. In his compelling analysis, Nigel Kettley develops an alternative approach to theory building in educational research, and explores a radical new system for facilitating the growth of knowledge.